Collaborative Models for Community-Driven Industrial Education: Enhancing Workforce Development Through Partnership Programs in Malaysia - Akter, Farhana; Shakil, Md Rofi Uddin; Akter, Yeasmin; Fatema, Kanij; Afi, Noor Jannah Binti; Azizan, Norizan; Ab Hamid, Kamal (Information Management and Business Review, 2024)
This study analyses the value of collaborative education strategies for improving workforce development in Malaysia, focusing on collaborations between educational institutions and industry. In recent years, the Malaysian job market has experienced major challenges, especially in terms of graduate preparation for employment. Many graduates struggle due to inadequate skills and limited employment opportunities, emphasizing the critical need for comprehensive educational changes. These coordinated activities aim to bridge the education-industry divide by developing connections between academia and the business sector. Moreover, the study uses a qualitative approach, conducting in-depth interviews with industry managers to understand better the impact of partnership programs, government support, and community participation on workforce readiness. Through these interviews, the study emphasizes the importance of collaborative education in providing graduates with the skills and competencies they need to succeed in a competitive work market. The findings show that, while these collaborations significantly boost graduates’ employability and skill sets, issues such as unequal access to opportunities and an overreliance on government assistance remain. Furthermore, the analysis discovers gaps in the available literature, particularly in the context of Malaysia, emphasizing the need for further research targeted to this environment. Future research directions will include empirical investigations to quantify the impact of collaborative education initiatives, quantitative analyses to evaluate the efficacy of various programs, and policy recommendations to improve Malaysia’s workforce development and foster long-term economic growth. By addressing these issues, the study hopes to contribute to a more comprehensive understanding of how collaborative education may effectively bridge Malaysia’s skills gap.